Immune boosting functional components of natural foods and its health benefits - Jaspin Stephen; Dharini Manoharan; Mahendran Radhakrishnan (Food Production, Processing and Nutrition)
Abstract Naturally available foods contain nutrients like vitamins (A, C, E, and D), zinc, calcium, magnesium, folate iron, omega fatty acids, selenium, and phytochemicals that have profound protective effects (boosting immunity) on human from diseases. The critical component of obtaining incredible health is to maintain proper diet with healthy food, proper sleep, and regular exercise. This review is drafted with an aim to lay out the importance of consuming immune boosting foods, present various nutritional compounds available and their mechanism in maintaining immunity, and briefly discuss some of the exotic immunity building food sources, nutrients present, health benefits, and its utilization. Some of the immune-boosting foods like almonds, spinach, citrus fruits, avocado, red bell pepper, pomegranate, kiwi, garlic, ginger, and passion fruit are deliberated to have positive impact on ameliorating cancer, diabetics, heart disease, skin, eyesight, bone health, blood pressure, brain development, anti-stress, antimicrobial, antibacterial, antifungal, anti-aging, anti-allergenicity, antimalarial, anti-mutagenicity, and anti-inflammatory. This review on immune boosting foods further emphasizes on the need and proved the importance of consuming natural fruits, vegetables, nut, and meat products for strengthening the immune system. Thus, the consumption of immune boosting foods is mandatory for maintaining the health and protecting our body from harmful pathogen and degenerative diseases naturally. Novelty impact statement Exploring diet-health approach is very important in the domain of food for enhancing immune response and activation in humans. Natural food that has health and nutritional benefits has made a noteworthy influence on changing consumer's lifestyles. The immune-strengthening foods with proper dietary recommendation play a significant role to increase the immunity of people. Graphical Abstract